Robert Heinrich Johannes Sobotta (1869-1945): The Great Author of the Most Widely Used Anatomy Atlas in Medical Education - Önal, Vildan; Nteli Chatzioglou, Gkionoul; Gayretli, Özcan (European Journal of Therapeutics, 2024)
In 1904 Sobotta’s Atlas of Descriptive Human Anatomy was published for the first time. At that time still divided into three volumes and published by Verlag Lehmann in Munich, the atlas was completely revised in 1982 and restructured into two volumes. Although the atlas has been revised several times since it was first published almost a hundred years ago. After starting out in Berlin, Sobotta worked for twenty-one years at the Anatomical Institute in Würzburg. Here he spent most of his scientific work and created his most important works. A brief three-year stint as director of the Anatomical Institute at the University of Königsberg followed before Sobotta became director of the Anatomical Institute in Bonn in 1919, where he taught until his retirement. The study paper is intended to provide a more detailed insight into the life and work of the scientist, whose name is known to almost every physician and healthcare professional.